Feasibility of a Provincial Voluntary Reporting System for Work-Related Asthma in Ontario - Teresa To; Susan M Tarlo; Susan McLimont; Ted Haines; D Linn Holness; M Diane Lougheed; Gary M Liss; Lisa Cicutto (Canadian Respiratory Journal)
OBJECTIVE The Ontario Work-Related Asthma Surveillance System: Physician Reporting (OWRAS) Network was established in 2007 to estimate the prevalence of work-related asthma (WRA) in Ontario, and to test the feasibility of collecting data for cases of WRA from physicians voluntarily.